2012
DOI: 10.7439/ijbar.v3i8.695
|View full text |Cite
|
Sign up to set email alerts
|

Review of Reasons and Remedial Measures for Burnout During Residency Programme

Abstract: Burnout in health care professionals has gained significant attention over the last few decades. As a result of the intense emotional demands of the work environment, clinicians are particularly susceptible to developing burnout above and beyond usual workplace stress. Residency training, in particular, can cause a significant degree of burnout, leading to interference with individuals' ability. Overall, burnout is associated with a variety of negative consequences including depression, suicidal ideation, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…10 Also, it can help to produce desirable effects such as tolerance of ambiguity, self-confidence, and maturity, and it may stimulate the acquisition of knowledge and skills. 11 , 12 However, unhealthy or negative stress, which is referred to as excessive stress, can interfere with efficient learning, impair memory, increase anxiety, decrease sleep, cause eating habit-related problems, lead to accident proneness, and decrease problem-solving abilities. 13 , 14 Good personal coping skills can counter the effect of stress to a certain extent, so that the strain can be alleviated.…”
Section: Introductionmentioning
confidence: 99%
“…10 Also, it can help to produce desirable effects such as tolerance of ambiguity, self-confidence, and maturity, and it may stimulate the acquisition of knowledge and skills. 11 , 12 However, unhealthy or negative stress, which is referred to as excessive stress, can interfere with efficient learning, impair memory, increase anxiety, decrease sleep, cause eating habit-related problems, lead to accident proneness, and decrease problem-solving abilities. 13 , 14 Good personal coping skills can counter the effect of stress to a certain extent, so that the strain can be alleviated.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier also there are conflicting results in scientific literature about this finding. 6 Some studies showed that female residents scored significantly more burnout whereas other studies have shown the opposite and few studies reported no gender associations. 7 Thus, implications of this study is that biological factor of gender may not be a reasonable starting point for understanding and explaining burnout among medical interns.…”
Section: Discussionmentioning
confidence: 99%
“…5 Female students reportedly are more severely affected with Burnout but conflicting reports in literature. 6 Developing countries like India have difficult working and social conditions and examining burnout is important to address quality care and working conditions. Yet there is dearth of studies assessing Burnout in medical interns from India.…”
Section: Introductionmentioning
confidence: 99%
“…Lower prevalence of burnout in present study compared to a previous study of Bangal et al among residents which shows 0verall burnout to be 50% may be because residents have more duties and responsibilities than doctors who were already trained and residents are the one who deals with the patient directly from entry to exit from the hospital. 10 The Burnout in Indian doctors is very low compared to studies from Europe i.e. 43% of respondents scored high for EE burnout, 35% for DP and 32% for PA, with 12% scoring high burnout in all three dimensions and in another study the level of emotional exhaustion (37.4%), high level of depersonalization (45.6%) and low perception of personal accomplishment (50.3%) done in Turkey, this may be because most doctors in India in government Tertiary care setting do not have to deal with mundane issues like paperwork, insurance companies and regulatory bodies.…”
Section: Discussionmentioning
confidence: 99%
“…13 Supporting our study that female clinicians experienced more burnout than male counterparts in a study conducted among united nations has reports women physicians have a higher rate of depression than the general population opposingly in another study from Maharashtra Bangal et al showed that males experienced more burnout than females. 10,14 Several studies have found that female medical students, residents, and physicians are more depressed than their male counterparts because they have to manage both family and profession. [15][16][17][18][19] …”
Section: Discussionmentioning
confidence: 99%